A study on the effect of different lighting conditions of the growth and density of tetraselmis chuii. - Tadina, Elizabeth Grace Chua (1979.)
An experiment on the effect of four different lighting conditions namely; dark, alternate indoor-outdoor, and outdoor was performed in the laboratory using the unicellular green algae, Tetrasemis chuii Chu. Algal yield measured in terms of number of cells per cubic centimeter (cc) was high in the outdoor conditions, followed by alternate out-door-indoor, and indoor respectively. On the other hand, the algae raised under dark conditions gave a very low yield . Therefore, lighting conditions are very necessary for the multiplication of algal cells.
Research Paper (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Tetraselmis Chuii